Pengembangan Sistem Manajemen Proyek Menggunakan Metode Scrum Berbasis Android - Rizky Suhaimi; Nurudin Santoso; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Software house handles a variety of software projects to meet client demands and solve various problems. A project can be led by a project manager. Project managers can have the task of making schedules, monitoring project work, assigning tasks to workers and reporting results of work project. During project work, the project leader can't observe daily work from project workers. In addition, the requirement or features of the client may change or increase, resulting in increased time spent on the project and the workload becomes larger. From these problems making a project management system using Scrum is the solution provided. Scrum is an Iterative and Incremental framework because of its successive and gradual development in terms of features for developing object-oriented software. In this study, development method uses Rapid Application Development and is built on Android platform. Testing on this system uses validation testing, unit testing, and compatibility testing. In unit test obtained 13 test cases with valid status. Whereas for validation testing there were 61 test cases with all test cases having valid status. And compatibility test state that the system can operate well on android lollipop until nougat.